Short-term evaluation of non-absorbable microgranular hydroxyapatite infiltration in the guinea pig subepidermal abdominal region - Xavier, A.P. [UNESP]; Schellini, Silvana Artioli [UNESP]; Aragon, Flávio Ferrari [UNESP]; Padovani, C.R. [UNESP]; Taga, E.M. (Associação Brasileira de Divulgação Científica (ABRADIC), 2002)
Non-absorbable microgranular hydroxyapatite was infiltrated into the subepidermal abdominal region of guinea pigs in order to assess the possibility of using this material to correct deficiencies in orbital volume. Microgranular hydroxyapatite (2.0 ml) was subepidermally infiltrated into the abdominal region of 20 guinea pigs. The animals were divided into four experimental groups of 5 animals each, which were killed 7 (G1), 15 (G2), 30 (G3) and 60 (G4) days after infiltration. The area and the largest and smallest diameters of the nodules formed by infiltration were evaluated at the site of infiltration and histological examination was performed. The mean granuloma area was similar in all groups. Histopathological examination showed that the material remained isolated from surrounding tissues by a pseudocapsule that became denser throughout the experiment. A host reaction started with young fibroblastic tissue that evolved to dense tissue until cartilaginous tissue was formed in G4, progressively advancing towards the center of the granuloma from G1 to G4. Non-absorbable microgranular hydroxyapatite is an inert material that was well tolerated by the animals studied, with maintenance of the infiltrated volume, and may perhaps be useful to fill anophthalmic cavities.
Keywords: Infiltration; Microgranular hydroxyapatite; Guinea pigs; Histopathology